The following theorem is a property of the circumcircle mid-arc triangle which appears to be unknown.
We will be using standard notation: \lvert{BC}\rvert=a, \lvert{AC}\rvert=b, \lvert{AB}\rvert=c; \angle{BAC}=\alpha, \angle{ABC}=\beta and \angle{BCA}=\gamma; s for the semiperimeter; R for the circumradius and r for the inradius. If X, Y and Z are the vertices of a triangle, we denote its area [XYZ].
Problem. Let ABC be a triangle and I its Incenter. Denote \omega the circumcircle of ABC. Let AI intersect \omega again at D. Define E and F cyclically. Let U, V and W be the midpoints of DE, EF and FD, respectively. Let A' be the reflection of A with respect to V. Define B' and C' cyclically (see figure 1). Then
[DEF]=[ABC]+[A'B'C'].\tag{1}
 |
Figure 1 |
Lemma 1. If ABC is a triangle and DEF is its circumcircle mid-arc triangle, then
\boxed{\frac{[ABC]}{[DEF]}=\frac{2r}{R}.}\tag{2}
Proof. By property of inscribed angles, \angle{BAF}=\angle{ACF}=\frac12\gamma and \angle{CAE}=\frac12\beta. It follows that
\begin{aligned}&\angle{EAF}=\alpha+\frac12\beta+\frac12\gamma\\&=\pi-\beta-\gamma+\frac12\beta+\frac12\gamma\\&=\pi-\frac12(\beta+\gamma).\end{aligned}By the law of sines,
\frac{EF}{\sin{(\pi-\frac12(\beta+\gamma))}}=\frac{EF}{\sin{\frac12(\beta+\gamma)}}=\frac{AF}{\sin{\frac12\gamma}}.\tag{3}
Since \angle{AFC}=\beta and, again, by the law of sines,
\frac{AF}{\sin{\frac12\gamma}}=\frac{b}{\sin{\beta}}.\tag{4}
From (3) and (4) we get
EF=\frac{b\sin{\frac12(\beta+\gamma)}}{\sin{\beta}}=2R\sin{\frac12(\pi-\alpha)}=2R\cos{\frac12\alpha}.\tag{5}
Analogously, we can find that
DF=2R\cos{\frac12\beta}\qquad ED=2R\cos{\frac12\gamma}.\tag{6}
Note that \angle{DFC}=\frac12\alpha and \angle{EFC}=\frac12\beta, so \angle{DFE}=\frac12(\alpha+\beta). Then the area of DEF is given by
[DEF]=\frac{EF\cdot{DF}\sin{\frac12(\alpha+\beta)}}{2}=2R^2\cos{\frac12\alpha}\cos{\frac12\beta}\cos{\frac12\gamma}.\tag{7}
Elsewhere we have proved that s=4R\cos{\frac12\alpha}\cos{\frac12\beta}\cos{\frac12\gamma} (for a proof, see section 3, c), here). As the area of ABC can also be written as [ABC]=rs, we can rewrite it like this[ABC]=4Rr\cos{\frac12\alpha}\cos{\frac12\beta}\cos{\frac12\gamma}.\tag{8}
Dividing (8) by (7) we get
\frac{[ABC]}{[DEF]}=\frac{2r}{R}.
\square
Lemma 2. Let ABC be an triangle and H its orthocenter. Let l_a, l_b and l_c be the perpendicular bisectors of sides BC, AC and AB, respectively. Denote H_1, H_2 and H_3 the reflections of H around l_a, l_b and l_c, respectively. Then
\boxed{\frac{[H_1H_2H_3]}{[ABC]}=\frac{(a^2-b^2)(a^2-c^2)}{b^2c^2}+\frac{(a^2-c^2)(b^2-c^2)}{a^2b^2}-\frac{(a^2-b^2)(b^2-c^2)}{a^2c^2}.}\tag{9}
Proof. From figure 2, note that
HH_3=2(\frac{c}{2}-AC_1).\tag{10}
 |
Figure 2 |
Let CH intersect AB in C_1. Applying the law of sines in the triangle ACC_1, we have that
b=\frac{AC_1}{\sin{(\frac{\pi}{2}-\alpha)}}=\frac{AC_1}{\cos{\alpha}}.
So, AC_1=b\cos{\alpha}. Substituting in (10) and then substituting from the law of cosines \cos{\alpha}=\frac{b^2+c^2-a^2}{2bc} we have
HH_3=2(\frac{c}{2}-b\cos{\alpha})=c-2b\cos{\alpha}=\frac{a^2-b^2}{c}.
Similarly, we get that HH_1=\frac{b^2-c^2}{a} and HH_2=\frac{a^2-c^2}{b}. Now, note that
[H_1H_2H_3]=[HH_2H_3]+[HH_1H_2]-[HH_1H_3].\tag{11}
As HH_3 and HH_2 are perpendicular to l_c and l_a, respectively, then \angle{H_2HH_3}=\alpha and similarly \angle{H_2HH1}=\gamma. Thus, equation (11) can be written as follows
[H_1H_2H_3]=\frac{(a^2-b^2)(a^2-c^2)\sin{\alpha}}{2bc}+\frac{(a^2-c^2)(b^2-c^2)\sin{\gamma}}{2ab}-\frac{(a^2-b^2)(b^2-c^2)\sin{(\alpha+\gamma)}}{2ac}.\tag{12}
Dividing both sides of equation (12) by [ABC]=\frac12bc\sin{\alpha}=\frac12ab\sin{\gamma}=\frac12ac\sin{\beta} and taking into account that \sin{(\alpha+\gamma)}=\sin{(\pi-\beta)}=\sin{\beta}.
\frac{[H_1H_2H_3]}{[ABC]}=\frac{(a^2-b^2)(a^2-c^2)}{b^2c^2}+\frac{(a^2-c^2)(b^2-c^2)}{a^2b^2}-\frac{(a^2-b^2)(b^2-c^2)}{a^2c^2}.
\square
Note that the terms on the right hand side of the equation
(9) are the products of the
Mollweide's formulas. Substituting from Mollweide's formulas and applying the identity of sine of double angle, we can write the equation
(9) as follows
\boxed{\frac{[H_1H_2H_3]}{[ABC]}=\frac{\sin{(\alpha-\beta)}\sin{(\alpha-\gamma)}}{\sin{\gamma}\sin{\beta}}+\frac{\sin{(\alpha-\gamma)}\sin{(\beta-\gamma)}}{\sin{\alpha}\sin{\beta}}-\frac{\sin{(\alpha-\beta)}\sin{(\beta-\gamma)}}{\sin{\alpha}\sin{\gamma}}.}\tag{13}
Back to the main problem
It is well-known that the orthocenter of the circumcircle mid-arc triangle is the incenter of the reference triangle. So IB\perp{FD}. Moreover, because of properties of inscribed angles, \angle{IDF}=\angle{FCB}=\angle{FDB}=\frac12\gamma
and \angle{IFD}=\angle{CAD}=\angle{DAB}=\angle{DFB}=\frac12\alpha.
Hence, by ASA, DFI\cong{DFB}. As a consequence, I is the reflection of B around FD. As B' is the reflection of B around W, it follows that the perpendicular bisector of FD must also bisect IB', meaning that B' is the reflection of the orthocenter of DEF, I, around the perpendicular bisector of DF. Similarly, we conclude that A' and C' are the reflections of I around the perpendicular bisectors of EF and DE, respectively. Now our goal will be to show that \frac{[A'B'C']}{[DEF]}=1-\frac{2r}{R}. Note that \angle{EFD}=\frac12(\alpha+\beta), \angle{EDF}=\frac12(\beta+\gamma) and \angle{DEF}=\frac12(\alpha+\gamma). Applying formula (13) to triangles A'B'C' and DEF and substituting angles we have
\frac{[A'B'C']}{[DEF]}=\frac{\sin{\frac12(\alpha-\gamma)}\sin{\frac12(\beta-\gamma)}}{\cos{\frac12\beta}\cos{\frac12\alpha}}+\frac{\sin{\frac12(\beta-\gamma)}\sin{\frac12(\beta-\alpha)}}{\cos{\frac12\gamma}\cos{\frac12\alpha}}-\frac{\sin{\frac12(\alpha-\gamma)}\sin{\frac12(\beta-\alpha)}}{\cos{\frac12\gamma}\cos{\frac12\beta}}. \tag{14}
Note that the right hand side of the equation
(14) are, again, products of the
Mollweide's formulas. Thus, we have
\begin{aligned}\frac{[A'B'C']}{[DEF]}&=\frac{(a-c)(b-c)}{ab}+\frac{(b-c)(b-a)}{ac}-\frac{(a-c)(b-a)}{bc}\\&=1-\frac{c(a+b-c)}{ab}+1-\frac{b(a-b+c)}{ac}+1-\frac{a(-a+b+c)}{bc}.\end{aligned}\tag{15}
\begin{aligned}\frac{[A'B'C']}{[DEF]}&=3-\frac{2a\cos^2{\frac12\alpha}+2b\cos^2{\frac12\beta}+2c\cos^2{\frac12\gamma}}{s}\\&=1-\frac{a\cos{\alpha}+b\cos{\beta}+c\cos{\gamma}}{s}.\end{aligned}\tag{16}
Substituting from the law of sines, factorizing and applying double-angle identity for sine,
\begin{aligned}\frac{[A'B'C']}{[DEF]}&=1-\frac{R(\sin{2\alpha}+\sin{2\beta}+\sin{2\gamma})}{s}.\end{aligned}\tag{17}
But \sin{2\alpha}+\sin{2\beta}+\sin{2\gamma}=4\sin{\alpha}\sin{\beta}\sin{\gamma}=\frac{abc}{2R^3}=\frac{2rs}{R^2}, hence
\frac{[A'B'C']}{[DEF]}=1-\frac{R}{s}\left(\frac{2rs}{R^2}\right)=1-\frac{2r}{R}.\tag{18}
Finally, from (2) and (18),
[ABC]+[A'B'C']=\frac{2r}{R}[DEF]+\left(1-\frac{2r}{R}\right)[DEF]=[DEF].
\square
Some corollary inequalities:
- \frac{(a^2-b^2)(a^2-c^2)}{b^2c^2}+\frac{(a^2-c^2)(b^2-c^2)}{a^2b^2}\geq\frac{(a^2-b^2)(b^2-c^2)}{a^2c^2}. (follows from (9))
- \frac{\sin{(\alpha-\beta)}\sin{(\alpha-\gamma)}}{\sin{\gamma}\sin{\beta}}+\frac{\sin{(\alpha-\gamma)}\sin{(\beta-\gamma)}}{\sin{\alpha}\sin{\beta}}\geq\frac{\sin{(\alpha-\beta)}\sin{(\beta-\gamma)}}{\sin{\alpha}\sin{\gamma}}. (follows from (13))
- \frac{c(a+b-c)}{ab}+\frac{b(a-b+c)}{ac}+\frac{a(-a+b+c)}{bc}\leq3. (follows from (15)) (this is IMO, 1964/2)
- a\cos{\alpha}+b\cos{\beta}+c\cos{\gamma}\leq{s}. (follows from (16))
- \sin{2\alpha}+\sin{2\beta}+\sin{2\gamma}\leq\frac{s}{R}. (follows from (17))
- R\geq{2r}. (This is Euler's Inequality! It follows from (18))
Update. Van Khea has generalized my problem. I have given a proof of his nice generalization which is available at
Van Khea's areal problem.